Viral etiological causes of febrile seizures for respiratory pathogens (EFES Study). Issue 2 (1st February 2019) - Carman, Kursat Bora; Calik, Mustafa; Karal, Yasemin; Isikay, Sedat; Kocak, Ozan; Ozcelik, Aysima; Yazar, Ahmet Sami; Nuhoglu, Cagatay; Sag, Cigdem; Kilic, Omer; Dinleyici, Meltem; Lacinel Gurlevik, Sibel; et al.
ABSTRACT: Background : Febrile seizure is the most common childhood neurological disorder, is an important health problem with potential short- and long-term complications, also leading to economic burden and increased parental anxiety about fevers and seizures occurring in their children. There are no routine recommendation to detect etiological causes of FS for neurological perspective, further knowledge about the etiological causes of FS in children will support preventive measures and follow-up strategies. The aim of this study is to evaluate the percentage of respiratory viruses in children with FS. Methods : This prospective multicenter study, entitled " Viral etiological causes of febrile seizures for respiratory pathogens ( EFES Study )" examined representative populations in eight different cities in Turkey between March 1, 2016 and April 1, 2017. Nasopharyngeal swabs were taken from all children at presentation. A respiratory multiplex array was performed to detect for influenza A and B; respiratory syncytial virus A and B; human parainfluenza virus 1-2-3 and 4; human coronavirus 229E and OC43; human rhinovirus; human enterovirus; human adenovirus; human bocavirus; human metapneumovirus. Results : During the study period, at least one virus was detected in 82.7% (144/174) of children with FS. The most frequently detected virus was adenovirus, followed by influenza A and influenza B. Detection of more than one virus was present in 58.3% of the children with FS, and the most common co-existence was the presence of adenovirus and influenza B. In children younger than 12 months, Coronavirus OC43 was the most common, while influenza A was most frequently observed in children older than 48 months ( p < 0.05 ). Human bocavirus was common in children who experienced complex FS, while respiratory syncytial virus (RSV) A was more common in children who experienced simple FS. Influenza B virus was the most common virus identified in children who were experiencing their first incidence of FS ( p < 0.05 ). Conclusions : This study indicates that respiratory viruses are important in the etiology of FS in children. The results show that antibiotics must be prescribed carefully in children with FS since the majority of cases are related to viral causes. Widespread use of the existing quadrivalent influenza vaccine might be useful for the prevention of FS related to the flu. Further vaccine candidates for potential respiratory pathogens, including RSV, might be helpful for the prevention of FS.